Essay on the life and manners of Robert Grosseteste - Perry, Philip, 1720-1774 (Catholic Record Society publications. Records series ;, 2022)
"Philip Perry's Essay on the Life and Manners of the Venerable Robert Grosseteste presents us not only with a high standard of biographical scholarship but also a fine example of English eighteenth-century polemical writing. Grosseteste was a formidable thirteenth-century bishop of Lincoln who, because of his insistence upon the primacy of Scripture and his apparent wrangling with the papacy, had long been claimed as a type of proto-Protestant in the English post-Reformation historical tradition. Perry sets out in his Essay a vivid account of Grosseteste's life and achievements to advance his cause as a worthy saint and to recover his reputation as a loyal son of the Roman Church. His frank discussion of the abuses that Grosseteste opposed and the controversies in which he engaged put his text beyond the limits of what a Catholic priest could advisably print in eighteenth-century England. The manuscript remained unpublished for fear of causing scandal, and now sees its first printed edition." --